HUBUNGAN GAYA KEPEMIMPINAN DAN MOTIVASI DENGAN KINERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RS JIWA PROVINSI JAMBI - Fithriyani; Rino M (Melati Institute, 2023)
The quality of health services by nurses in providing nursing care is a reflection of nurses' performance. A person's performance can be influenced by fleadership and motivational actors. The purpose of the study was to determine the picture and relationship of leadership style and motivation with the performance of implementing nurses in the inpatient room of Jambi Provincial Hospital. This study used a type of quantitative research with a descriptive analytical design, using a cross sectional approach. The research site is at Jambi Provincial Mental Hospital, with 36 implementing nurses. The implementation time is carried out from September 2022 to June 2023. Data analysis using univariate and bivariate analysis with chi-square test. The expected target output is that the performance of the implementing nurse can improve with a good leadership style and motivation. The results of the study obtained an overview of the leadership style of the head of the room in the inpatient room of Jambi Provincial Hospital that the autocratic leadership style was strong 66.7%, democratic 52.8% and laizess 63.9%, the motivation of the implementing nurse in the inpatient room of Jambi Provincial Hospital was more than half the motivation of nurses 52.8% good, the performance of implementing nurses in the inpatient room of Jambi Provincial Hospital was mostly good 61.1% nurse performance. Bivariate analysis found no relationship between leadership style and motivation with the performance of the implementing nurse in the inpatient room of Jambi Provincial Hospital.